An analytical method for assessing the live load deformation of a suspension bridge with an improved central buckle. (January 2023) - Zhang, Wen-ming; Chen, Yu-peng
Abstract: Suspension bridges lack favorable supports for global vertical stiffness, making it challenging to meet the road safety requirement due to the excessive deflection of stiffening girder when developing towards larger spans. It hinders the development of the ultimate span of suspension bridges and reduces the utilization rate of materials. This paper proposes an improved central buckle (ICB) to increase the global vertical stiffness of suspension bridges. Without changing the constraints of the stiffening girder, the central buckle and horizontal cable are placed at the mid-span and bottom of the stiffening girder, respectively, which combination is referred to as ICB. It restrains the horizontal displacement of the main cable and reduces the maximum deflection of the suspension bridge due to the asymmetric live loads. The analytical expressions of the deflection and girder-end rotation of the suspension bridge with the ICB are derived based on the deflection theory. The expression of the variable equivalent horizontal spring stiffness of the ICB is proposed and verified by a finite element model of the suspension bridge. These results prove that the ICB can effectively restrain the horizontal displacement of the main cable caused by the asymmetric live load and significantly reduce the vertical deflection of the stiffening girder. The performed parametric analysis clarified the mechanism of increasing the vertical stiffness of the suspension bridge based on the ICB force transmission path, providing a new design scheme for improving the global vertical stiffness of the suspension bridge and expanding its upper span limit.